UNDERSTANDING CAREER CHOICE BASED ON INER FAMILY PARENTING “ROE PERSONALITY THEORY” - Yurita Tiro; Afdal Afdal; A Muri Yusuf (Widyagogik, 2021)
Parents are the first place for students to get education, whether or not children are confident, whether or not children are confident, the ability to choose children is very influential from how families provide guidance to children, how parenting styles are from small children until they are able to think for themselves how good it is for their children. himself, based on several parenting styles, something that is shown in helping to improve and support good child development for a child is democratic parenting. This article aims to discuss career guidance in the implementation of career choices based on parenting patterns, family environment on the tendency of students' career choices, which will be seen based on the Roe Personality Career Theory developed by Anna Roe which is a theory belonging to the selection theory. career based on personality and needs. In the article using the literature review approach method (literature research), this article will describeexplain to provide an understanding of scientific journal analysis that is relevant to the discussion and the material that has been selected, the main material in the analysis of the literature review of sources related and related to the topics discussed. By understanding Career Guidance Theory based on Roe's Theory, we can know that the importance of parenting for children will be the background for how children will continue their lives, career choices in the future (Future).